2021
DOI: 10.1038/s41598-021-84210-z
|View full text |Cite
|
Sign up to set email alerts
|

Glial cell type-specific gene expression in the mouse cerebrum using the piggyBac system and in utero electroporation

Abstract: Glial cells such as astrocytes and oligodendrocytes play crucial roles in the central nervous system. To investigate the molecular mechanisms underlying the development and the biological functions of glial cells, simple and rapid techniques for glial cell-specific genetic manipulation in the mouse cerebrum would be valuable. Here we uncovered that the Gfa2 promoter is suitable for selective gene expression in astrocytes when used with the piggyBac system and in utero electroporation. In contrast, the Blbp pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 59 publications
0
20
0
Order By: Relevance
“…To make pPB-gfa2-DTA, the EGFP of pPB-gfa2-EGFP was replaced with DTA. pPB-CAG-EGFP ( 53 ) and pCAG-sFGFR3 ( 31 ) were described previously. pPB-CAG-loxP-ER T2 CreER T2 -loxP-FGF8-IRES2-EGFP was made by inserting loxP-ER T2 CreER T2 -loxP developed by M. G. Holt and FGF8-IRES2-EGFP derived from pCAG-FGF8 ( 33 ) and pIRES2-EGFP (Clontech) into the pPB-CAG vector.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To make pPB-gfa2-DTA, the EGFP of pPB-gfa2-EGFP was replaced with DTA. pPB-CAG-EGFP ( 53 ) and pCAG-sFGFR3 ( 31 ) were described previously. pPB-CAG-loxP-ER T2 CreER T2 -loxP-FGF8-IRES2-EGFP was made by inserting loxP-ER T2 CreER T2 -loxP developed by M. G. Holt and FGF8-IRES2-EGFP derived from pCAG-FGF8 ( 33 ) and pIRES2-EGFP (Clontech) into the pPB-CAG vector.…”
Section: Methodsmentioning
confidence: 99%
“…The sections were then subjected to Hoechst 33342 staining. The PLP probe, the FGFR2 probe, and the FGFR3 probe were described previously ( 31 , 53 ).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, these lines may differ in multiple ways from native astrocytes and wild-type mice. In contrast, infection of postnatal brain with adeno-associated viruses (AAVs) and delivery of transposon-based reporters to embryonic brain by electroporation are relatively efficient methods for labeling astrocyte-lineage cells in vivo ( Figure 3 ) [ 141 , 142 , 143 ]. Fusing astroglial cell type-specific promoters to fluorescent proteins with piggyBac transposon can directly label targeted subpopulations permanently or within defined developmental phases [ 143 ], while recombinases driven by cell type-specific promoters can both efficiently label and alter the genome of astrocytes [ 144 ].…”
Section: Microscopic Imaging Of Astrocyte Developmentmentioning
confidence: 99%
“…In contrast, infection of postnatal brain with adeno-associated viruses (AAVs) and delivery of transposon-based reporters to embryonic brain by electroporation are relatively efficient methods for labeling astrocyte-lineage cells in vivo ( Figure 3 ) [ 141 , 142 , 143 ]. Fusing astroglial cell type-specific promoters to fluorescent proteins with piggyBac transposon can directly label targeted subpopulations permanently or within defined developmental phases [ 143 ], while recombinases driven by cell type-specific promoters can both efficiently label and alter the genome of astrocytes [ 144 ]. Hamabe-Horiike et al revealed that the Gfa2 -promoter labeled nearly 80% of astrocytes, the Plp1 -promoter labeled nearly 96% of oligodendrocytes, and the Mbp -promoter labeled nearly 90% of oligodendrocytes at E15 electroporation, whereas the CAG -promoter labeled nearly 40% of neurons, 15% of astrocytes, and 8% of oligodendrocytes [ 143 ].…”
Section: Microscopic Imaging Of Astrocyte Developmentmentioning
confidence: 99%
See 1 more Smart Citation